1983
DOI: 10.1104/pp.72.3.817
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Responses in Cultured Plant Cells

Abstract: The response of suspension-cultured pear (Pyrus communes cv Bartlett) cells to heat stress was studied using three viability tests: regrowth (culture growth during 10 days after stress); triphenyltetrazolium chloride reduction; and electrolyte leakage. Critical (50% injury) temperatures for a 20-minute exposure were 420, 52°, and 560C, respectively, for these viability tests. Electrolyte Plant responses to superoptimal temperature include inhibition of photosynthesis (2, 4), pollination (5), protein synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Knowledge initial study (15). The culture medium and most methods (culture maintenance, growth conditions and measurement, heat stress treatment, and viability tests) were as described previously (15 (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge initial study (15). The culture medium and most methods (culture maintenance, growth conditions and measurement, heat stress treatment, and viability tests) were as described previously (15 (13,14).…”
mentioning
confidence: 99%
“…The culture medium and most methods (culture maintenance, growth conditions and measurement, heat stress treatment, and viability tests) were as described previously (15 (13,14). Our procedure (15) involved pipetting aliquots to test tubes for imposition of heat stress. We found that handling (transfer by pipette) influenced heat sensitivity (Fig.…”
mentioning
confidence: 99%
“…In the experiments for Figure 2, zero time measurements could not be obtained. However, without the handling involved in HS treatment, 22°C-grown cells showed less than 15% survival of a 43°C, 20-min stress (13). Heat tolerance was fully maintained for 2 d at 22°C and then began to gradually decline (Fig.…”
Section: Methodsmentioning
confidence: 98%
“…All experiments were conducted with suspension-cultured cells of pear (Pyrus communis cv Bartlett) which were used in our previous studies (13,14). The culture medium and most methods (culture maintenance, growth conditions and measurement, heat stress treatment, and viability tests) were as described before (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation